2010
DOI: 10.1111/j.1365-2958.2010.07443.x
|View full text |Cite
|
Sign up to set email alerts
|

Processing of metacaspase into a cytoplasmic catalytic domain mediating cell death in Leishmania major

Abstract: Metacaspases are cysteine peptidases that could play a role similar to caspases in the cell death programme of plants, fungi and protozoa. The human protozoan parasite Leishmania major expresses a single metacaspase (LmjMCA) harbouring a central domain with the catalytic dyad histidine and cysteine as found in caspases. In this study, we investigated the processing sites important for the maturation of LmjMCA catalytic domain, the cellular localization of LmjMCA polypeptides, and the functional role of the cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
61
2
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 57 publications
4
61
2
8
Order By: Relevance
“…We also showed for TcMCA5 that its C-terminal extension negatively regulates its ability to promote an apoptotic-like cell death based on its catalytic activity (Figures 2 and 5), suggesting that active TcMCA5 may have a pro-apoptotic role regulated by proteolytic processing of its C-terminal extension, as recently described for LmjMCA by Zalila et al 11 The observed difference in phenotypes for TcMCA5 and TcMCA5DCt overexpressors seems not to be due to a different subcellular distribution of the protein (data not shown), but could be attributed to an enhanced activity, as the artificial deletion of the C-terminal extension in TcMCA5 increases its catalytic efficiency by 2.7-fold. On the other hand, the C terminus might maintain the protein in a different conformation, preventing the cleavage activation of proapoptotic proteins.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We also showed for TcMCA5 that its C-terminal extension negatively regulates its ability to promote an apoptotic-like cell death based on its catalytic activity (Figures 2 and 5), suggesting that active TcMCA5 may have a pro-apoptotic role regulated by proteolytic processing of its C-terminal extension, as recently described for LmjMCA by Zalila et al 11 The observed difference in phenotypes for TcMCA5 and TcMCA5DCt overexpressors seems not to be due to a different subcellular distribution of the protein (data not shown), but could be attributed to an enhanced activity, as the artificial deletion of the C-terminal extension in TcMCA5 increases its catalytic efficiency by 2.7-fold. On the other hand, the C terminus might maintain the protein in a different conformation, preventing the cleavage activation of proapoptotic proteins.…”
Section: Discussionsupporting
confidence: 81%
“…5 Their substrate specificity is for basic residues at P1 position, making them unable to cleave caspase substrates. 6 Evidences suggest that metacaspases modulate cell death, [7][8][9][10][11] cell cycle progression [12][13][14] and protein aggregation, 15 but there is still controversy about their functions and their relation with caspases. [16][17][18] The fact that metacaspases are not present in humans and fulfil important roles in trypanosomatids make them attractive drug targets, and a first series of inhibitors with trypanocidal activity has been developed recently.…”
mentioning
confidence: 99%
“…In plants, metacaspases are essential for embryogenesis (5, 6) and have been shown to act in antagonistic relationships, functioning as both positive and negative regulators of PCD (7). In yeast and some protozoa, metacaspases have been implicated as mediators of cell death in response to oxidative stress and environmental change (3,(8)(9)(10).Various attempts have been made to draw parallels between caspases and metacaspases in respect to structure, activation, and function (11). However, two striking differences between metacaspases and caspases are their substrate specificities and requirements for activation.…”
mentioning
confidence: 99%
“…In plants, metacaspases are essential for embryogenesis (5, 6) and have been shown to act in antagonistic relationships, functioning as both positive and negative regulators of PCD (7). In yeast and some protozoa, metacaspases have been implicated as mediators of cell death in response to oxidative stress and environmental change (3,(8)(9)(10).…”
mentioning
confidence: 99%
See 1 more Smart Citation